Ultrasound-induced inertial cavitation from gas-stabilizing nanoparticles - Kwan, JJ; Graham, S; Myers, R; Carlisle, R; Stride, E; Coussios, CC (American Physical Society, 2015)
The understanding of cavitation from nanoparticles has been hindered by the inability to control nanobubble size. We present a method to manufacture nanoparticles with a tunable single hemispherical depression (nanocups) of mean diameter 90, 260, or 650 nm entrapping a nanobubble. A modified Rayleigh-Plesset crevice model predicts the inertial cavitation threshold as a function of cavity size and frequency, and is verified experimentally. The ability to tune cavitation nanonuclei and predict their behavior will be useful for applications ranging from cancer therapy to ultrasonic cleaning.